Stigma and fear during the COVID-19 pandemic: a qualitative study on the perceptions of healthcare workers in Canada and Singapore - Christine Fahim; Christine Fahim; Chou Chuen Yu; Jeanette Cooper; Suvabna Theivendrampillai; Taehoon (Tom) Lee; Michelle Wai-Ki Lau; Christine Marquez; Bernard Tang; Mathews Mathew; Malika Sharma; Malika Sharma; et al. (Frontiers in Public Health)
IntroductionWe sought to explore healthcare providers (HCPs)' perceptions of and experiences with stigma during the COVID-19 pandemic in Canada and Singapore.MethodsWe conducted a qualitative study (May 2020–February 2021) with HCPs in Canada and Singapore and developed a semi-structured interview guide rooted in the Health Stigma and Discrimination Framework (HSDF). We recruited participants online and through word of mouth via newsletters, blogs and social media. Participants were eligible to participate if they worked as a healthcare provider in Singapore or Canada during COVID-19. Following participant consent, data were recorded, transcribed verbatim, and coded using a framework approach. Coded data were charted into a framework matrix and used to compare themes in each country.ResultsWe conducted 51 interviews (23 in Canada; 28 in Singapore). HCPs perceived that patient fears coupled with mistrust of the health system impacted health behaviors. HCPs reported discrimination and stigmatization of population subsets. In Singapore, this included Chinese tourists and migrant workers and in Canada, this included people of Chinese ethnicity and people experiencing homelessness. This stigma was often attributed to pre-existing prejudices including perceptions that these populations were at increased risk of COVID-19 or not adhering to public health recommendations. HCPs feared spreading COVID-19 to family, peers and patients, often resulting in participants choosing to isolate from social circles. HCPs in both countries experienced occupation-based stigma, including stigma related to public health practices (masking, testing); in Canada, this intersected with race-based prejudice for participants of Chinese ethnicity. HCPs in both samples witnessed and experienced stigmatizing behavior; some participants also experienced discrimination.ConclusionsSecondary stigma related to occupation was experienced by HCPs during COVID-19. HCPs experienced intersecting stigma based on race/ethnicity and observed stigmatization of marginalized patient populations. Most themes were consistent across Canada and Singapore. Strategies to mitigate COVID-19 related stigma toward HCPs and at-risk patient populations are warranted.